Stabilization and release of palm tocotrienol emulsion fabricated using pH-sensitive calcium carbonate - Phui, Yee Tan; Beng, Ti Tey; Eng, Seng Chan; Lai, Oi Ming; Hon, Weng Chang; Tai, Boon Tan; Liu, Yuanfa; Wang, Yong; Chin, Ping Tan (MDPI AG, 2021)
Calcium carbonate (CaCO3) has been utilized as a pH-responsive component in various products. In this present work, palm tocotrienols-rich fraction (TRF) was successfully entrapped in a self-assembled oil-in-water (O/W) emulsion system by using CaCO3 as the stabilizer. The emulsion droplet size, viscosity and tocotrienols entrapment efficiency (EE) were strongly affected by varying the processing (homogenization speed and time) and formulation (CaCO3 and TRF concentrations) parameters. Our findings indicated that the combination of 5000 rpm homogenization speed, 15 min homogenization time, 0.75% CaCO3 concentration and 2% TRF concentration resulted in a high EE of tocotrienols (92.59–99.16%) and small droplet size (18.83 ± 1.36 µm). The resulting emulsion system readily released the entrapped tocotrienols across the pH range tested (pH 1–9); with relatively the highest release observed at pH 3. The current study presents a potential pH-sensitive emulsion system for the entrapment and delivery of palm tocotrienols.